The Sale and Purchase of Non-Cash Gold at Tokopedia from an Islamic Perspective - Anif Mafatihur Rohmah (Journal of Law, Society, and Islamic Civilization, 2022)
Tokopedia is one of the leading marketplaces in Indonesia that allows Tokopedia users (Toppers) to buy and save gold digitally in small amounts. This article aims to analyze the permissibility of buying and selling gold in cash in an Islamic perspective. This research uses normative legal research or library research, namely legal research conducted by examining library materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials. This research is expected to provide insight into the mechanism of buying and selling gold transactions in cash so that people can avoid fraud.